La “verosimilitud del derecho invocado”: falta de uniformidad de criterios para su análisis advertida en la jurisprudencia y doctrina nacional, y una propuesta inicial para uniformizarla - Quispe Quesada, Jhonatan Jose Paolo (2024)
This thesis shows the existence of a problem in the analysis that judges do for granting of precautionary protection, specifically, when they evaluate the requirement called “plausibility of the right invoked” in each specific case. Evidence of this problem is drawn from various judicial decisions issued on the matter. Although the Peruvian legal system, local doctrine and judges according to their jurisprudence, share a conception of the fumus boni iuris and its importance as a requirement for granting of precautionary measures; in the reality, there is no uniform analysis methodology for this. This lack of uniformity produces negative effects on various fundamental rights that are developed in this work. Recognizing the existence of this problem, an analysis scheme of the “plausibility of the right invoked” is proposed that can contribute to the establishment of a general methodology for evaluating that requirement, for those requests for granting of precautionary measures that present before the process has begun or before the existence of a non-final sentence. The application of this proposal can be observed through various examples developed in this thesis. The proposal will be justified by contrasting it with other methodologies offered by local doctrine, as well as explaining its coherence with the dogmatic conception of fumus boni iuris, its harmonious integration with the current functioning of precautionary protection in the Peruvian legal system, and the benefits that can report.